Phantoms para ultrasonido con variación continua de la velocidad de propagación de la onda - Rivera Cardona, Marissa A.; Reiszel Pereira, Fernando; Pereira, Wagner C.A.; Machado, João Carlos (Revista Mexicana de Ingenieria Biomedica, 2002)
Ultrasound (US) phantoms are generally used to mimic the acoustic properties of human tissue and thus provide a better understanding of the interaction of sound with tissue. Wave propagation velocity (WPV) is considered constant in commercial US phantoms, around 1,540 m/s. In the human body, the WPV varies according to the type of tissue, between 1,450 m/s and 1,650 m/s. US phantoms in which WPV varies will provide additional information on the US behavior besides the one provided by the conventional US phantoms. In this work, four procedures, to construct US phantoms with WPV profiles, are presented. The first two methods use polymer and epoxy resin as base materials. In the second method, tungsten powder is added to the epoxy resin in order to provide a variation of the mixture WPV. On the third and fourth methods, respectively, distilled water and ethyl alcohol are used as the basic materials, in which ethilenoglycol is added to increase the WPV. Phantoms echogenicity is acquired by adding silica particles (0.8 mm diameter) to the mixture during the curing process. The method with the best result is presented and its results discussed.